Actuation of Liquid Crystalline Elastomers at or Below Ambient Temperature. (20th May 2022) - Bauman, Grant E.; McCracken, Joselle M.; White, Timothy J.
Abstract: Liquid crystal elastomers (LCE) are an emerging class of material actuators. LCE undergo macroscopic dimensional changes when subjected to a stimulus. The large stimuli‐response of LCE is associated with thermotropic disruption of order. Historically, comparatively high temperatures are required to disrupt orientation in LCE to achieve meaningful work output. Here, we introduce an approach to prepare LCE via thiol‐Michael/thiol–ene reactions that actuate at or below ambient temperature. Alignment was imparted to the LCE by mechanical alignment and 3D printing. The LCE materials detailed here achieve strains of 40 % with a maximum deformation rate of 6.5 % °C −1 . The functional utility of the tunability of the thermotropic response of these materials is illustrated in reconfiguration triggered via body heat and sequential actuation of a multi‐material element. Abstract : Liquid crystal elastomers with actuation temperatures at or below ambient temperature are prepared via a sequential thiol‐Michael/thiol–ene reaction scheme based on the monomer C6BAPE. The reduction in actuation temperature is accompanied by an increase in actuation rate (>6 % °C −1 ). The low actuation temperatures achieved are promising for use in many applications at ambient temperature or below.